Guided Internet-based versus face-to-face clinical care in the treatment of tinnitus: a multicentre randomized non-inferiority trial - Beukes, Eldre W.; Andersson, Gerhard; Allen, Peter M.; Manchaiah, Vinaya; Baguley, David (American Medical Association, 2018)
Importance: Accessible clinical care is not always available to those with distressing tinnitus. Internet-based cognitive behavioural therapy has potential to increase access to evidence-based tinnitus services. Research comparing the effectiveness of this intervention with face to face care is required. Objective: To evaluate whether an Internet-based cognitive behavioural therapy intervention is at least as effective as established individualized face-to-face care in reducing tinnitus distress and tinnitus-related difficulties. Design: A randomized, multi-centre, two-arm parallel group, non-inferiority trial with 2-month follow-up was run between October 2016 and July 2017. Participants were randomly assigned (1:1) to either intervention using variable permuted block sizes of four and six. Setting: The experimental group received the Internet-intervention online while the active control undertook the usual face-to-face tinnitus care at one of three UK-based National Health Service hospitals. Participants: Adults that had been referred to their local tinnitus clinics due to bothersome tinnitus, were invited to participate (n =374). 92 participants were randomized (experimental n = 46; control n= 46), of which 88 completed the immediate post-intervention assessment and 72 completed follow-up assessment measures. Interventions: Participants were randomized to receive either 8 weeks of guided Internet-based cognitive behavioural therapy or 2-3 individualized face-to-face appointments in a tinnitus clinic. Main Outcome measures: The primary outcome was a change in tinnitus distress (as assessed by the Tinnitus Functional Index). Secondary assessment measures were included for insomnia, anxiety, depression, hearing disability, hyperacusis, cognitive failures, and satisfaction with life. Results: The between-group difference in the Tinnitus Functional Index scores at post-intervention of 5.19 (95% CI -4.17 to 14.53) and 5.18 (95% CI -4.17 to 14.53) at follow-up, fell within the non-inferiority margin of 13 points for the lower 95% confidence interval. For the secondary outcomes, only outcomes for insomnia fell outside the non-inferiority margin, at both post-intervention and follow-up, favouring the iCBT group. Conclusions and Relevance: This is the first trial to compare an Internet-based intervention with standard individualized care for tinnitus. It demonstrates that both interventions were equally effective for reducing tinnitus distress and most tinnitus-related difficulties. Trial Registration Clinicaltrials.gov: Identifier: NCT02665975